Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

A circle with centre at the point (2,-1) passes through the point A at (4,-5).

(a) Find an equation for the circle C.

(b) Find an equation of the tangent to the circle C at the point A, giving your answer in the form ax+by+c=0, where a, b, and c are integers..




Sagot :

Answer:

a)

[tex](x - 2) {}^{2} + (x +1) {}^{2} = 20[/tex]

b)

[tex]x - 2y - 14 = 0[/tex]

Step-by-step explanation:

a) the centre is (2,-1)

the equation so far is:

[tex](x - 2) {}^{2} + (x +1) {}^{2} = r {}^{2}[/tex]

because you just change the sign of 2 to -2 and change the sign of -1 to +1

to find the radius:

[tex]r = \sqrt{(change \: in \: x) {}^{2} + (change \: in \: y) {}^{2} }[/tex]

[tex]r = \sqrt{(4 - 2) {}^{2} + ( - 5 - ( - 1)) {}^{2} } [/tex]

[tex]the \: radius \: is \: 2 \sqrt{5} [/tex]

to find diameter square 2√5

[tex](2 \sqrt{5} \:) {}^{2} = 20 \\ the \: equation \: is(x - 2) {}^{2} + (x +1) {}^{2} = 20[/tex]

b) find the gradient between the points (2,-1) and (4,-5)

[tex]gradient = \frac{change \: in \: y}{change \: in \: x} [/tex]

[tex]\: gradient = \frac{ - 5 + 1}{4 - ( - 1)} = - 2[/tex]

the gradient of the tangent is the negative reciprocal of -2. This means you flip it upside down which would be -1/2, then multiply by -1 which is 1/2

the gradient is 1/2

using the gradient and the point (4,-5) to write the equation in the form y=mx+c

here y is -5, m is the gradient (1/2) and x is 4

we need to work out c

[tex]y = mx + c[/tex]

[tex] - 5 = \frac{1}{2} (4) + c[/tex]

[tex]- 5 = 2 + c[/tex]

subtract 2 on both sides

[tex]- 5 - 2 = c[/tex]

[tex]c = - 7[/tex]

now the equation is

[tex]y = \frac{1}{2} x - 7[/tex]

but we need to write it in the form ax+by+c=0

subtract y on both sides:

[tex]\frac{1}{2} x - y - 7 = 0[/tex]

multiply everything by 2 to get rid of the fraction

[tex]x - 2y - 14 = 0[/tex]

that is the final equation

Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.